Dampak fatherless terhadap perkembangan anak dan faktor penyebab dalam keluarga di indonesia - Dzakiyah, Nadiyatudz (Maliki Interdisciplinary Journal, 2026)
The phenomenon of fatherlessness has become increasingly prominent in Indonesia due to various factors such as divorce, paternal death, family conflict, work-related absence, and limited paternal involvement influenced by patriarchal cultural norms. This study aims to analyze the impact of fatherlessness on children's development—specifically emotional, psychological, social, and behavioral aspects—and to identify the contributing factors behind its emergence in Indonesian families. A review of previous studies shows that fatherlessness is associated with low self-esteem, emotional dysregulation, difficulties in forming interpersonal relationships, and a higher risk of behavioral problems. Children may also experience father hunger, a profound sense of loss toward the father figure that affects their psychological stability. Contributing factors include structural issues such as divorce and paternal death, as well as cultural influences that restrict fathers' roles to financial providers, leading to emotional absence. This study highlights the importance of fathers’ physical and emotional involvement in child-rearing and recommends collaboration among families, social institutions, and policymakers to prevent and mitigate the negative effects of fatherlessness.